Current practices of long term athlete development of junior athletes in high performance sport environments - McKeown, I.; Ball, N. (Journal of Australian Strength and Conditioning, 2013)
The purpose of this study was to report the current practices and application of long term athlete development theory within elite athlete pathways. Sixty-five strength and conditioning coaches, sport scientists and other professionals participated by completing an electronic survey. The survey elicited information about awareness, understanding and use of common athlete development models. Seventy-two percent of the respondents apply some elements of long term athlete development theory. The most commonly understood model is Balyi`s LTAD model. There is awareness of alternative models; however these are not as deeply understood. Additional questions were asked regarding the use of movement assessment and performance testing in junior athletes. All respondents reported the use of some form of performance assessment, with strength and power assessment most common. Movement assessments are also widely used, however no set methodology is preferred with the majority of practitioners using their own modified versions of published assessment tools. The survey shows that within high performance sport there is an understanding of long term athlete development and the various performance and movement assessments that can aid in programming and coaching decisions; however there is a strong desire for further research into these areas and their practical application in the development of elite athletes.